2012
DOI: 10.4056/sigs.2696029
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of Thauera aminoaromatica strain MZ1T

Abstract: Thauera aminoaromatica strain MZ1T, an isolate belonging to genus Thauera, of the family Rhodocyclaceae and the class the Betaproteobacteria, has been characterized for its ability to produce abundant exopolysaccharide and degrade various aromatic compounds with nitrate as an electron acceptor. These properties, if fully understood at the genome-sequence level, can aid in environmental processing of organic matter in anaerobic cycles by short-circuiting a central anaerobic metabolite, acetate, from microbiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…As a reference, the ANIm value between Azoarcus sp. CIB and a strain of the closely related Thauera genus, T. aminoaromatica MZ1T strain [23], was 84.34% (aligned 18.47%). Therefore, these data strongly suggest that strain CIB is indeed a bacterial species different to those sequenced so far.…”
Section: Phylogeny Of Azoarcus Strainsmentioning
confidence: 98%
“…As a reference, the ANIm value between Azoarcus sp. CIB and a strain of the closely related Thauera genus, T. aminoaromatica MZ1T strain [23], was 84.34% (aligned 18.47%). Therefore, these data strongly suggest that strain CIB is indeed a bacterial species different to those sequenced so far.…”
Section: Phylogeny Of Azoarcus Strainsmentioning
confidence: 98%
“…The first strain in this genus for which a completely sequenced genome was obtained was Thauera aminoaromatica MZ1T, which was isolated from activated sludge samples from an industrial wastewater treatment facility (7). The strain is noted for its ability to degrade various aromatic compounds and for production of abundant exopolysaccharide (11). …”
Section: Genome Announcementmentioning
confidence: 99%
“…Previous studies demonstrated that many species in the genus Thauera are able to use acetate in the reduction of various electron acceptors, for example, in the reduction of selenite by T. selenatis (Lowe et al 2010). Thauera aminoaromatica MZ1T can metabolize acetate to methane (Jiang et al 2012). To our knowledge, there are only a few bacteria possessing the ability to oxidize acetate for humus and Fe(III) reduction, e.g., the iron-reducing bacterium Geobacter sp.…”
Section: Humus and Fe(iii) Reductionmentioning
confidence: 98%
“…The genera Thauera and Geobacter share some metabolic features. Both are capable of mineralizing aromatic compounds (Jiang et al 2012) and contain abundant cyt c (Lowe et al 2010). However, Thauera species are facultatively anaerobic while Geobacter species are obligately anaerobic.…”
Section: Humus and Fe(iii) Reductionmentioning
confidence: 99%